Antibacterial activities of agave angustifolia and pittosporumferrugineum - Ainil Farhan, M.U.; Lee, P.C.; How, S.E.; Jualang Azlan Gansau (Hibiscus Publisher, 2013)
Methanolic extracts and liquid – liquid partition extracts of Agave angustifolia and Pittosporum ferrugineum were tested against Escherichia coli(E. coli), Staphylococcus aureus (S. aureus), Streptococcus pneumoniae (S. pneumoniae), Enterobacteraerogenes (E. aerogenes), Bacillus cereus (B. cereus), Pseudomonas aeruginosa (P. aeruginosa) and Salmonella typhi (S. typhi) for their antibacterial activity. Ethyl acetate extract (EAE) of Agave angustifolia exhibited strongest activities against S. aureus, S. pneumoniae, B. cereus, P. aeruginosa and S. typhi, while aqueous extract (AQE) of Pittosporum ferrugineum exhibited strongest antibacterial activities against S. aureus, S. pneumoniae, B. cereus, and P. aeruginosa.